Transnational environmental crime - White, R. D. (Robert Douglas), 1956- (Farnham, Surrey, England : Ashgate, 2013)
The essays selected for this volume illustrate the growing interest in and importance of crime that is both environmental and transnational in nature. The topics covered range from pollution and waste to biodiversity and wildlife crimes, and from the violation of human rights associated with the exploitation of natural resources through to the criminogenic implications of climate change. The collection provides insight into the nature and dynamics of this type of crime and examines in detail who is harmed and what can be done about it. Differential victimisation and contemporary developments in environmental law enforcement are also considered. Collectively, these essays lay the foundations for a criminology that is forward looking, global in its purview, and that deals with the key environmental issues of the present age. Show more Show less.
Part I. Thinking about transnational environment crime -- Part II. Conflict, victimisation and the environment -- Part III. Pollution and waste -- Part IV. Biodiversity and wildlife crime -- Part V. Combating transnational environmental crime -- Index.
Includes bibliographical references and index.
Keywords: Offenses against the environment; Transnational crime; Crime prevention -- International cooperation; Police -- International cooperation